Features of the operation of the training stand “Electric vehicle motor” in determining the operation characteristics of electric transport - A. R. Safin; Z. M. Shakurova; L. V. Dolomanyuk; V. A. Gavrilov; N. V. Denisova (Известия высших учебных заведений: Проблемы энергетики)
In the modern world, the problem of the ecological state of our planet is acute. The environmental situation depends on many factors, these include both natural phenomena and human actions. One solution to this problem is to replace traditional internal combustion engines with more environmentally friendly electric vehicles.THE PURPOSE. The objective of this study is to analyze the internal structure of an electric vehicle, based on the training stand “Electric Vehicle Motor”, as well as to study the functions of this device, located at the Kazan State Energy University.METHODS. The authors of the article processed and analyzed the capabilities of modern laboratory equipment that simulates the operation of a particular component of an electric vehicle.RESULTS. The technology of the laboratory bench operating the electric vehicle, together with the DVT Customer software, allows for full control of the electric motor, as well as monitoring and changing a large number of parameters that affect the operation of the entire device as a whole.CONCLUSION. Since electric vehicles are gaining more and more popularity every year, the demand for people capable of diagnosing, repairing, and even improving existing ones and developing new components and assemblies in the field of electric vehicles is growing significantly. Using the “Electric Vehicle Motor” stand for teaching technical subjects and conducting research work can serve as a good basis for the formation of a general knowledge base about electric transport, its structure, the operating principle of all the main elements, monitoring and diagnostics of an electric vehicle.